2015
DOI: 10.1021/acs.jctc.5b00650
|View full text |Cite
|
Sign up to set email alerts
|

Chromophore–Protein Coupling beyond Nonpolarizable Models: Understanding Absorption in Green Fluorescent Protein

Abstract: The nature of the coupling of the photoexcited chromophore with the environment in a prototypical system like green fluorescent protein (GFP) is to date not understood, and its description still defies state-of-the-art multiscale approaches. To identify which theoretical framework of the chromophore-protein complex can realistically capture its essence, we employ here a variety of electronic-structure methods, namely, time-dependent density functional theory (TD-DFT), multireference perturbation theory (NEVPT2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
122
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(134 citation statements)
references
References 129 publications
8
122
0
Order By: Relevance
“…For a generalization beyond a few-state model, see Refs. 40,41. Regardless the debated interpretation of this term as a dispersion effect, 39,[42][43][44] a nonresonant excitonic coupling between subsystems 41,45 or a resonant coupling, 46 it is a manifestation of the mutual correlation of the electrons in the subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…For a generalization beyond a few-state model, see Refs. 40,41. Regardless the debated interpretation of this term as a dispersion effect, 39,[42][43][44] a nonresonant excitonic coupling between subsystems 41,45 or a resonant coupling, 46 it is a manifestation of the mutual correlation of the electrons in the subsystems.…”
Section: Introductionmentioning
confidence: 99%
“…26−29 Such a polarizable embedding (QM/MMpol) scheme has been combined with coupled cluster theory (CC), 23,26,30,31 the complete-active-space self-consistent field (CASSCF) method, 32 and time-dependent density functional theory (TDDFT) 27,28,33,34 and has provided a very effective description of excitation energies beyond static multipole models, 23,34−37 allowing the systematic study of different polarization effects induced in the ground state and in response to the excitation of the solute. 15,25 Here, we combine for the first time quantum Monte Carlo (QMC) methods with the reaction field of polarizable dipoles and investigate the performance of QMC/MMpol for the computation of the excitation energies of small solvated molecules, namely, methylenecyclopropene and acrolein in water. The use of QMC to compute electronic excitations has already been extensively validated in the gas phase 21,38−41 and also employed in combination with standard MM methods 17,21,25 and DFT embedding.…”
Section: Introductionmentioning
confidence: 99%
“…Recently,D aday et al performed calculations of the absorption spectrumo ft he green fluorescentp rotein. [93] To reproduce the experimentally observed influenceo ft he environment on the excitation energies, these authors found it necessary not only to combine point charges and polarisable dipolesa tt he CASSCF/MMpol level in the ground-state and the excited-state, but also to add an estimated dispersion-correction term based on the LR TD-DFT results. This inspired us to address the disagreement by similarly adding an empirical dispersion term [Eq.…”
Section: Explicitsolvent Modelsmentioning
confidence: 99%